Twenty-four Hours Stay After Colorectal Surgery; A Systematic Review - Smalbroek, Bo P.; Schuffel, Inger-Lise; Weijs, Teus J.; Dijksman, Lea M.; Poelmann, Floris B.; Wijffels, Niels A.T.; Boerma, Djamila; Smits, Anke B. (Journal of Coloproctology, 2023)
Introduction The introduction of Enhanced Recovery After Surgery led to increasing twenty-four hours discharge pathways, for example in laparoscopic cholecystectomy and bariatric surgery. However, implementation in colorectal surgery still must set off. This systematic review assesses safety and feasibility of twenty-four hours discharge in colorectal surgery in terms of readmission and complications in current literature. Secondary outcome was identification of factors associated with success of twenty-four hours discharge.Methods Pubmed and EMBASE databases were searched to identify studies investigating twenty-four hours discharge in colorectal surgery, without restriction of study type. Search strategy included keywords relating to ambulatory management and colorectal surgery. Studies were scored according to MINORS score.Results Thirteen studies were included in this systematic review, consisting of six prospective and seven retrospective studies. Number of participants of the included prospective studies ranged from 5 to 157. Median success of discharge was 96% in the twenty-four hours discharge group. All prospective studies showed similar readmission and complication rates between twenty-four hours discharge and conventional postoperative management. Factors associated with success of twenty-four hours discharge were low ASA classification, younger age, minimally invasive approach, and relatively shorter operation time.Conclusions Twenty-four hours discharge in colorectal surgery seems feasible and safe, based on retro- and prospective studies. Careful selection of patients and establishment of a clear and adequate protocol are key items to assure safety and feasibility. Results should be interpreted with caution, due to heterogeneity. To confirm results, an adequately powered prospective randomized study is needed.
Keywords: ERAS; ambulatory; 24 hours discharge; twenty-four hours stay; hospitalization; colorectal